Syncretism in Vodu and Orisha: An Anthropological Analysis - Montgomery, Eric James (The journal of religion & society, 2016)
This article is a comparative and ethnographic analysis of syncretism as a theoretical tool for explaining "African-based" religions (Vodu and Orisha) in West Africa and the New World. Vodu and Orisha defy syncretism as a valid concept for explaining the creativity of ritual life because it fails to account for the historicity, the religious imagination, or the cultural context of these forms. This article discusses that despite many shortcomings and problems with syncretism as a concept, it continues to be employed across many disciplines, even as it conflates and mystifies the different aspects and elements of African religions. Syncretism approaches tend to mystify African symbols and explain away things that, from the inside, are fundamental to African systems. This article will explain and contextualize many of these flaws and deficiencies with the concept through fieldwork and archival research.